2016
DOI: 10.18632/oncotarget.12610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of BRCA1/BRCA2 mutations in a Brazilian population sample at-risk for hereditary breast cancer and characterization of its genetic ancestry

Abstract: BackgroundThere are very few data about the mutational profile of families at-risk for hereditary breast and ovarian cancer (HBOC) from Latin America (LA) and especially from Brazil, the largest and most populated country in LA.ResultsOf the 349 probands analyzed, 21.5% were BRCA1/BRCA2 mutated, 65.3% at BRCA1 and 34.7% at BRCA2 gene. The mutation c.5266dupC (former 5382insC) was the most frequent alteration, representing 36.7% of the BRCA1 mutations and 24.0% of all mutations identified. Together with the BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 53 publications
6
55
2
1
Order By: Relevance
“…Most Latin American studies identified a higher rate of BRCA1 than BRCA2 mutations [37], however studies from Costa Rica [43], Cuba [50], Puerto Rico [51] and Uruguay [46] reported the opposite finding. However, prevalence information could be underestimated due to methodology procedures.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 93%
See 4 more Smart Citations
“…Most Latin American studies identified a higher rate of BRCA1 than BRCA2 mutations [37], however studies from Costa Rica [43], Cuba [50], Puerto Rico [51] and Uruguay [46] reported the opposite finding. However, prevalence information could be underestimated due to methodology procedures.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 93%
“…Several recent studies have evaluated BRCA mutation in Latin American countries, and some of them have documented prevalence studies in high-risk population and in unselected invasive BC cases in Mexico (six total studies, 6.3-23.0% in high risk, 4.3% in unselected) [34][35][36], Brazil (eight studies, 3.4-22.5%, 2.3%) [37][38], Argentina (two studies, 16.2-58.3%, unknown) [33,39], Colombia (five studies, 14.3-24.5%, 1.2-4.5%) [40][41], Chile (two studies, 7.1-20.4%, unknown) [42], Costa Rica (one study, 4.5%, unknown) [43], Cuba (one study, 2.6%, unknown) [44], Peru (one study, 4.9%, unknown) [45], Uruguay (one study, 17%, unknown) [46], Venezuela (one study,17.2%, unknown) [47], Trinidad and Tobago (one study, unknown, 10.4%) [48] and The Bahamas (one study, 27.1%, unknown) [49]. Most Latin American studies identified a higher rate of BRCA1 than BRCA2 mutations [37], however studies from Costa Rica [43], Cuba [50], Puerto Rico [51] and Uruguay [46] reported the opposite finding.…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 99%
See 3 more Smart Citations